Bio-inspired fabrication of adsorptive ultrafiltration membrane for water purification: Simultaneous removal of natural organic matters, lead ion and organic dyes - Sarper Sarp (Journal of Environmental Chemical Engineering, 2023)
Conventional ultrafiltration membrane is difficult to achieve the multi-component removal of water contaminants including macromolecules and small ions. Meanwhile, a large number of petrochemical-based polymers as membrane material is raising concerns about environmental risk. In this study, we present a feasible way for the manufacture of multifunctional cellulose-based nanocomposite membranes via bio-fabrication by Acetobacter xylinus for water purification. The harvested bacterial cellulose (BC) pellicle was coated by polydopamine (PDA) as a functional layer and molecular linker to immobilize carboxylated cellulose nanocrystals (C-CNCs) to prepare BC/PDA14h/CNCs membrane (BCM/PDA14h/CNCs). The composited PDA and C-CNCs on the BC nanofibers endowed the membrane with a maximum adsorption capacity of up to 167.80 mg g−1 for Pb2+, and 251.58 mg g−1 for methylene blue (MB). Multiple contaminants (heavy metals, organic dyes, and natural organic matter (NOM)) can also be treated by BCM/PDA14h/CNCs simultaneously during the dynamic filtration process. The removal efficiency of BCM/PDA14h/CNCs against the mixture of metal ions is inversely proportional to the radius of hydrated ions. The selective separation studies on binary dye mixtures showed that the separation efficiency of the membrane is mainly related to the electronegativity of dyes. The BCM/PDA14h/CNCs exhibited preferential adsorption for cationic dyes, with a separation efficiency was up to 98%. Dynamic fouling experiments confirmed that the BCM/PDA14h/CNCs presented excellent antifouling performance and showed a high flux recovery ratio. The multifunctional characteristic, high removal efficiency, excellent reusability and stability as well as environmentally friendly feature of the prepared membrane in the present study provide a sustainable approach for membrane fabrication and promising application in water purification.